Pengaruh Kepuasan Pelanggan Terhadap Loyalitas Pada Penggunaan Produk Outdoor - Pratama, Putra Bayu; , Dr. Anton Agus Setyawan, SE, M.Si (2016)
This research aims to determine the effect of customer satisfaction on loyalty to the use outdoor. The sample product used in this research is among the students who use outdoor products in Surakarta totaling 100 responden.The sampling in this study using a convenience sampling. From the results of data analysis and discussion, it can be concluded that customer satisfaction is positive and significant impact on customer loyalty. This is evident from the results of the t test which scored 10.235 tarithmetic accepted at significance level of 5%. High customer satisfaction, the higher customer loyalty. Conversely the lower the customer satisfaction, the lower the customer loyalty. Loyal customers generally will continue to purchase the brand although faced with many alternative brands of competitors' products that offer services that are superior characteristics. When many customers from a brand of outdoor products in this category means the outdoor product brand has strong brand power. Keywords: Customer satisfaction, customer loyalty, brand preferences.